Characteristics of hormonal profile of children with allergic diseases - Shumna T.Ye. (Medičnì Perspektivi)
With the purpose to determine features of hormonal type in children with allergic diseases, the levels of adrenocorticotropic hormone (ACTH), thyroid-stimulating hormone (TSH) and cortisol were investigated in 110 children in the age from 6 to 17 years. Of them 79 children with allergic diseases (40 children from Zaporozhye and 39 children – from eco¬friendly clean Primorsk and Berdyansk districts of the Zaporozhye area) and 31 healthy children (16 children - from Zaporozhye and 15 - with conventionally ecofriendly clean districts of the Zaporozhye area). Levels of hormones (ACTH (pg/ml), TSH (mkIU/ml), cortisol (ng/ml) were determined through diagnostic test systems by a standard method in laboratories of the Zaporozhуe state medical university. By research results it is set, that in the conditions of large industrial city Zaporozhуe, forming of allergic pathology in children took place during activating of the hypophysis-adrenal system with the increase of TSH, cortisol, ACTH secretion with a high risk of exhaustion of immunoreactions and persistence of antigens; this was confir¬med by increase of values of their medians in relation to healthy children. In children with allergic diseases, habitants of ecologically favourable Primorsk and Berdyansk districts of the Zaporozhye area, vice versa, lower indexes of medians of ACTH, TSH and cortisol were registered; this testifies to sup¬pression of hypothalamus function and hypophysis system with violation of protective reaction and adaptation mechanisms in response to forming of allergic inflammation. Thus, adjusting of hormonal activity by principle of ne¬gative reverse link in children with allergic diseases was not executed, regardless of place of residence. In addition, indexes of median of ACTH, TSH, cortisol in children with different clinical forms of allergic diseases (bronchial asthma, allergic rhinitis, atopic dermatitis) in comparison to healthy ones, testified that for children with bronchial asthma the highest level of index of medians of ACTH (37,39 (29,1-56,11) pg/ml) and cortisol (249,23 (169,57-293,83) ng/ml) was registered, for children with a rhin¬allergosis – indexes of medians of cortisol were the lowest (84,69 (84,06-92,81) ng/ml), and indexes of medians of TSH were reliably higher only in comparing groups of children with bronchial asthma (2,73 (1,13-3,18) mkMU/ml) with healthy (1,96 (1,59-1,99) mkMU/ml). As a result of the conducted research, it was well-proven that indexes of hormonal type in children with allergic diseases depend not only on their place of residence but also on the clinical forms of allergic pathology; this must be taken into account in individual selection of doses and duration of treatment even by inhalation and by topical glucocorthicosteroid agents.